Free‐moving artificial eggs containing temperature loggers reveal remarkable within‐clutch variance in incubation temperature. (2nd July 2018) - Hope, Sydney F.; DuRant, Sarah E.; Hallagan, John J.; Beck, Michelle L.; Kennamer, Robert A.; Hopkins, William A.
Abstract : Incubation is a crucial aspect of avian parental care and measuring incubation temperature in the wild can improve our understanding of life history tradeoffs and inform conservation efforts. However, there are challenges associated with measuring the temperature of eggs in natural nests. Most studies to date have measured incubation temperature by using a single, stationary logger in each nest. However, real eggs are rotated and moved throughout the nest by the parent during the incubation period, and thus, a stationary logger may not accurately represent the temperature experienced by individual eggs within the entire clutch. We recorded incubation temperature in nests by using multiple, mobile artificial egg temperature loggers. We installed six mobile loggers and one stationary logger in wood duck Aix sponsa nests to compare the two logger types in the field. We found that at a given ambient temperature, mobile loggers recorded lower average and more variable temperatures than stationary loggers. Further, temperatures recorded by stationary loggers showed no relationship with clutch size, while mobile loggers captured temperatures that were lower and more variable as clutch size increased. Also, the multiple mobile loggers revealed that eggs within a nest experienced a substantial range of temperatures throughout the incubation period. We discuss potential limitations of this method, but believe that it is a promising way to collect biologically‐relevant incubation temperature data and provides an opportunity to advance our understanding of incubation temperature as a parental effect.